Writing architecture in modern Italy : narratives, historiography, and myths - Ricchi, Daria (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Writing Architecture in Modern Italy tells the history of an intellectual group connected to the small but influential Italian Einaudi publishing house between the 1930s and 1950s. It concentrates on a diverse group of individuals including Bruno Zevi, an architectural historian and politician; Giulio Carlo Argan, an art historian; Italo Calvino, a fiction writer; Giulio Einaudi, a publisher; and Elio Vittorini and Cesare Pavese, both writers and translators. Linking architectural history and historiography within a broader history of ideas, this book proposes four different methods of writing history, defining historiographical genres, modes, and tones of writing that can be applied to history writing to analyse political and social moments in time. It identifies four writing genres: myths, chronicles, history, and fiction, that became accepted as forms of multiple postmodern historical stories after 1957. An important contribution to the architectural debate, Writing Architecture in Modern Italy will appeal to those interested in the history of architecture, history of ideas and architectural education"--
OCLC-licensed vendor bibliographic record.
Keywords: Giulio Einaudi editore; Historiography -- Italy -- History -- 20th century; Architecture -- Historiography; Architectural criticism -- Italy -- History -- 20th century; ARCHITECTURE / General